2020
DOI: 10.3390/nu12020588
|View full text |Cite
|
Sign up to set email alerts
|

Positive Association of Dietary Inflammatory Index with Incidence of Cardiovascular Disease: Findings from a Korean Population-Based Prospective Study

Abstract: Recently, diets with higher inflammatory potentials based on the dietary inflammatory index (DII®) have been shown to be associated with increased cardiovascular disease (CVD) risk in the general population. We aimed to prospectively investigate the association between the DII and CVD risk in the large Korean Genome and Epidemiology Study_Health Examination (KoGES_HEXA) cohort comprised of 162,773 participants (men 55,070; women 107,703). A validated semi-quantitative food frequency questionnaire (SQ-FFQ) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 49 publications
5
19
1
Order By: Relevance
“…A large cohort study in Korea (n = 162,773) found that DII was associated with a higher risk of developing CVD in men but not in women. 139 Similarly, in the previously mentioned study by Park et al, 132 DII was associated with CVD mortality in men across all ethnic groups, whereas in women the relationship was present only in Caucasian and Japanese Americans but not Hawaiian, Latino, or African Americans. 132 In contrast, the DII was also associated with a higher risk of self-reported hypertension in the Australian Longitudinal Study on Women's Health (n = 7169).…”
Section: Longitudinal Studiesmentioning
confidence: 65%
“…A large cohort study in Korea (n = 162,773) found that DII was associated with a higher risk of developing CVD in men but not in women. 139 Similarly, in the previously mentioned study by Park et al, 132 DII was associated with CVD mortality in men across all ethnic groups, whereas in women the relationship was present only in Caucasian and Japanese Americans but not Hawaiian, Latino, or African Americans. 132 In contrast, the DII was also associated with a higher risk of self-reported hypertension in the Australian Longitudinal Study on Women's Health (n = 7169).…”
Section: Longitudinal Studiesmentioning
confidence: 65%
“…The energy‐adjusted dietary inflammatory index (E‐DII) was developed to measure an individual's dietary inflammatory potential (Shivappa et al, 2014). There have been an increasing number of studies reporting the associations between the E‐DII score and a variety of inflammatory diseases and conditions, including diabetes mellitus (Laouali et al, 2019), cardiovascular disease (Khan et al, 2020), metabolic syndrome (Kim et al, 2018), cognitive impairment (Frith et al, 2018), and chronic kidney disease (Mazidi et al, 2018). In a cross‐sectional study conducted in the U.S. population, the E‐DII score was positively associated with the number of missing teeth (Kotsakis et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The results of the present study are consistent with a study by Imran khan et al who carried out a cohort study on 1111 subjects to evaluate the relationship between DIP and cardiovascular disease (CVD). The results showed no a signi cant correlation between DIP and CVD in females while a signi cant relationship was found in male subjects [42]. Similarly, Gabriela Pocovi-Gerardino et al conducted a crosssectional study on 105 women with a mean age of 45.4 years old and found no signi cant correlation between the DIP score and CVD markers [43].…”
Section: Discussionmentioning
confidence: 93%